2013
DOI: 10.1590/s1982-56762013000100012
|View full text |Cite
|
Sign up to set email alerts
|

Fontes de fosfito e acibenzolar-S-metílico associados a fungicidas para o controle de doenças foliares na cultura da soja

Abstract: RESUMOO objetivo deste trabalho foi estudar diferentes fontes comerciais de fosfito e acibenzolar-S-metílico (ASM) seguidos de uma aplicação de fungicida no controle do míldio, do oídio e da ferrugem asiática, para reduzir o número de aplicações de fungicidas e aumentar o espectro de controle das doenças da soja. Foram conduzidos dois experimentos na região de Ponta Grossa, PR, nas safras 2006/07 e 2007/08. O delineamento experimental utilizado foi de blocos casualizados com quatro repetições. Os tratamentos f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
4
12
0
11
Order By: Relevance
“…Similar results have also been verified by other authors such as Lins et al (2011), who observed a decrease in AUDPC when phosphite was applied in mangoes (Mangifera indica L.) to control Lasiodiplodia theobromae. Silva et al (2013), while evaluating soybean (Glycine max L.), found that K phosphite and Mn significantly reduced the AUDPC of mildew and had no effect on powdery mildew and Asian soybean rust.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results have also been verified by other authors such as Lins et al (2011), who observed a decrease in AUDPC when phosphite was applied in mangoes (Mangifera indica L.) to control Lasiodiplodia theobromae. Silva et al (2013), while evaluating soybean (Glycine max L.), found that K phosphite and Mn significantly reduced the AUDPC of mildew and had no effect on powdery mildew and Asian soybean rust.…”
Section: Resultsmentioning
confidence: 99%
“…O Brasil é o segundo maior produtor mundial da cultura, obtendo na safra 2017/18 a produção de 119,2 milhões de toneladas, com uma produtividade média das lavouras brasileiras de 3.394 kg ha -1 (CONAB 2019). No entanto, a ocorrência de doenças foliares é um dos principais fatores de redução da produtividade e qualidade do grão, sendo um desafio constante para os sojicultores (SILVA et al 2013). Dentre as doenças, o oídio (Microsphaera diffusa Cke.…”
Section: Introductionunclassified
“…Microsphaera diffusa é um parasita obrigatório que tem capacidade de infectar a parte aérea da planta de soja, incluindo hastes, pecíolo e vagem, no entanto, sua ocorrência é mais comum nas folhas (SILVA et al 2013, YULIA et al 2017. A sua patogênese, inicia com a deposição dos seus conídios sobre a folha, que germinam e infectam as células da epiderme e posteriormente o micélio coloniza a superfície foliar, resultando em uma camada de micélio branco e pulverulento.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Phosphite application induces an immediate response from the plant against the pathogen (11). Several studies conducted in Brazil have reported the efficiency of using phosphites, either alone or with other products, for a number of diseases, including downy mildew in onion (24), yellow and brown spot disease in wheat (18), and powdery mildew and Asian soybean rust in soybean crops (21).…”
Section: Introductionmentioning
confidence: 99%